Determinans Of Students’ Interest In Enterpeneurship : Students’ In Perpectives In Medan - Romindo M Pasaribu; Juara Simanjuntak; Sri Ida Simanjuntak; Desman Telambanua; Vinsensius Matondang (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
In economic growth, entrepreneurship is able to increase per capita income and reduce poverty levels and remains an important pillar in achieving a country's economic development. The Indonesian government through Presidential Regulation (Perpes) No. 2 of 2022 states that it is able to create 1 million new entrepreneurs. Basically, entrepreneurial intention is the best determinant in a country's economic development through entrepreneurship. This study aims to explore what factors influence the entrepreneurial intention of students in 5 universities in Medan City. The results showed that behavioral beliefs have a significant effect on personal attitudes, normative beliefs have a significant effect on subjective norms, control beliefs have a significant effect on perceived behavior, personal attitudes, subjective norms, perceived behavior, social support, and current behavior have a significant effect on entrepreneurial intentions. Personal attitudes are unable to mediate the effect of behavioral beliefs on entrepreneurial intention, perceived behavior and subjective norms mediate the effect of controlling beliefs on entrepreneurial intention. This research extends the understanding of the theory of planned behavior. It serves as a basis to demonstrate the need to create more inclusive and equitable strategies to support the entrepreneurial spirit among university students in Medan.